The effect of polymerization cycles on porosity of microwave-processed denture base resin - Compagnoni, Marco Antonio [UNESP]; Barbosa, D. B.; de Souza, R. F.; Pero, Ana Carolina [UNESP] [UNESP] (Mosby, Inc, 2004)
Statement of problem. Although most of the physical properties of denture base resin polymerized by microwave energy have been shown to be similar to resins polymerized by the conventional heat polymerization method, the presence of porosity is a problem.Purpose. This study evaluated the effect of different microwave polymerization cycles on the porosity of a denture base resin designed for microwave polymerization.Material and methods. Thirty-two rectangular resin specimens (65 X 40 X 5 mm) were divided into 3 experimental groups (A, B, and C; Onda-Cryl, microwave-polymerized resin) and I control group (T; Classico, heat-polymerized resin), according to the following polymerization cycles: (A) 500 W for 3 minutes, (B) 90 W for 13 minutes + 500 W for 90 seconds, (C) 320 W for 3 minutes + 0 W for 4 minutes + 720 W for 3 minutes, and (T) 74degreesC for 9 hours. Porosity was calculated by measurement of the specimen volume before and after its immersion in water. Data were analyzed using 1-way analysis of variance (alpha = .05).Results. The mean values and SDs of the percent mean porosity were: A = 1.05% +/- 0.28%, B = 0.91% +/- 0.15%, C = 0.88% +/- 0.23%, T = 0.93% +/- 0.23%. No significant differences were found in mean porosity among the groups evaluated.Conclusion. Within the limitations of this study, a denture base resin specifically designed for microwave Polymerization tested was not affected by different polymerization cycles. Porosity was similar to the conventional heat-polymerized denture base resin tested.